EDTA-Modified Carbapenem Inactivation Method: a Phenotypic Method for Detecting Metallo-β-Lactamase-Producing Enterobacteriaceae - Sfeir, M. M. (J Clin Microbiol, 2019)
The increase in the prevalence and impact of infections caused by carbapenemase-producing Enterobacteriaceae is a global health concern. Therefore, rapid and accurate methods to detect these organisms in any clinical microbiology laboratory, including those in resource-limited settings, are essential to prevent and contain their spread. It is also important to differentiate between serine- and metal-dependent carbapenemases elaborated by carbapenemase-producing isolates for epidemiologic, infection control and prevention, and therapeutic purposes. Here, we describe the development and evaluation of the EDTA-modified carbapenem inactivation method (eCIM), an assay for discriminating between serine- and metal-dependent (i.e., metallo-β-lactamases [MBLs]) carbapenemases when used in conjunction with the modified carbapenem inactivation method (mCIM). The eCIM had an overall sensitivity and specificity of 100% and was adopted by the Clinical and Laboratory Standards Institute as a method to use in combination with the mCIM to identify MBL-producing Enterobacteriaceae.